Creating social value for the "base of the pyramid": an integrative review and research agenda - Lashitew, Addisu A. (Journal of business ethics, 2022)
A growing body of research looks into business-led efforts to create social value by improving the socio-economic well-being of Base of the Pyramid (BoP) communities. Research shows that businesses that pursue these strategies - or BoP businesses - face distinct sets of challenges that require unique capabilities. There is, however, limited effort to synthesize current evidence on the mechanisms through which these businesses create social value. We systematically review the literature on BoP businesses, covering 110 studies published in business and management journals. We start by using bibliographic analysis to map the broad contours of the literature in terms of its common theoretical and empirical approaches, intellectual core, and evolution in time. We subsequently conduct a qualitative content analysis on the identified articles to synthesize their main findings. The analysis leads to a conceptual framework that explicates the antecedents, constraints, capabilities, and contingencies that drive social value creation. In addition to providing a rich and systematically organized account of the evidence, our analysis provides a critical reflection on the ethical dilemmas of social value creation efforts for the BoP, and outlines promising avenues for future research.